PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA PT MATAHARI DEPARTMENT STORE MALL CIPUTRA CIBUBUR - Evi Permatasari; Supardi Supardi; Agus Dharmanto (CV. Adiba Aisha Amira, 2024)
This study aims to analyze the influence of transformational leadership on employee performance through job satisfaction at PT Matahari Department Store Mall Ciputra Cibubur. Using a quantitative method, data were collected from 100 employees through a census method via interviews and questionnaires. The results of the study indicate that transformational leadership has a positive impact on job satisfaction, while job satisfaction also positively affects employee performance. Path analysis shows that job satisfaction plays a mediating role in the relationship between transformational leadership and employee performance. The conclusion of this study provides an overview that the development of transformational leadership can enhance job satisfaction and employee performance, contributing to increased company productivity. The practical implications of these findings provide a foundation for companies to implement leadership strategies that support employee well-being and optimal performance outcomes.